Lessons learned from 40 novel PIGA patients and a review of the literature. (26th May 2020) - Bayat, Allan; Knaus, Alexej; Pendziwiat, Manuela; Afenjar, Alexandra; Barakat, Tahsin Stefan; Bosch, Friedrich; Callewaert, Bert; Calvas, Patrick; Ceulemans, Berten; Chassaing, Nicolas; Depienne, Christel; Endziniene, Milda; et al.
Abstract: Objective: To define the phenotypic spectrum of phosphatidylinositol glycan class A protein ( PIGA )‐related congenital disorder of glycosylation (PIGA‐CDG) and evaluate genotype‐phenotype correlations. Methods: Our cohort encompasses 40 affected males with a pathogenic PIGA variant. We performed a detailed phenotypic assessment, and in addition, we reviewed the available clinical data of 36 previously published cases and assessed the variant pathogenicity using bioinformatical approaches. Results: Most individuals had hypotonia, moderate to profound global developmental delay, and intractable seizures. We found that PIGA‐CDG spans from a pure neurological phenotype at the mild end to a Fryns syndrome–like phenotype. We found a high frequency of cardiac anomalies including structural anomalies and cardiomyopathy, and a high frequency of spontaneous death, especially in childhood. Comparative bioinformatical analysis of common variants, found in the healthy population, and pathogenic variants, identified in affected individuals, revealed a profound physiochemical dissimilarity of the substituted amino acids in variant constrained regions of the protein. Significance: Our comprehensive analysis of the largest cohort of published and novel PIGA patients broadens the spectrum of PIGA‐CDG. Our genotype‐phenotype correlation facilitates the estimation on pathogenicity of variants with unknown clinical significance and prognosis for individuals with pathogenic variants in PIGA .